Romania's Integration into European Markets: Implications for Sustainability of the Current Export Boom - Kaminski, Bartlomiej (World Bank, Washington, D.C., 2013)
In defiance of its unimpressive track in structural reforms and relatively low foreign direct investment (FDI) inflows, Romanian exports have experienced surprisingly strong performance in both European Union (EU) and non-EU markets since 2000 after a four-year period of flat growth. While the first phase of growth in 1992-95 can be easily explained by redirection of trade toward the EU once the state monopoly over foreign trade was abolished and other policy areas liberalized, the current second phase of export expansion raises questions concerning its drivers and sustainability. Having examined overall foreign trade performance, evolving patterns of specialization, Romania's competitiveness in EU sunrise markets, changes in factor intensities of trade with the EU, and "intra-product" trade, the authors conclude that Romania's export offer has become diversified, reflecting an impressive progress in industrial restructuring. Restructuring has been facilitated by FDI inflows, even though they appear to have been too small to generate such a big effect. Romanian firms have become increasingly part of international production networks and traditional global value chains. Sustainability of this performance depends on maintaining macroeconomic stability and keeping wage increases in line with productivity growth, as well as increasing Romania's ability to attract larger FDI inflows through improvements in business climate and trade facilitation.